Pengaruh Jumlah Tenaga Kerja, Ekspor, Investasi Dan Kredit Perbankan Sektor Pertanian Terhadap Produk Domestik Regional Bruto (PDRB) Sektor Pertanian Provinsi Aceh - Anita Faiziah; Sofyan Sofyan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
ABSTRACT. The aim of this study is to analyse the influence of the number of the agricultural labours, agricultural export, agricultural investment and agricultural bank credit toward the agricultural GRDP of Aceh province. The independent variables are the agricultural labours, agricultural export, agricultural investment and agricultural bank credit and the dependent variable is the agricultural GRDP of Aceh province. The data that are used in this study are time series data which are taken from 1999-2012. This study method also use the Ordinary Least Square (OLS) method. The result shows that the variables of agricultural export, agricultural investment and agricultural bank credit have positively affected and highly significant toward the agricultural GRDP of Aceh province, where as the number of the agricultural labours has negatively affected and highly significant toward agricultural GRDP of Aceh province. Closeness of the correlation between the dependent variable and the independent variables that affect the agricultural GRDP of Aceh province is amounted to 89.7% which can be explained by the four variables in the model. The remaining 10.3% is explained by other factors outside the model's equations.